2006
DOI: 10.2116/analsci.22.1297
|View full text |Cite
|
Sign up to set email alerts
|

Application of Total Reflection X-ray Fluorescence Spectrometry to Small Glass Fragments

Abstract: Total reflection X-ray fluorescence spectrometry (TXRF) has been applied for trace elemental analysis of small glass fragments. A small glass sample (a fragment with weight less than 0.5 mg) was decomposed by 100 μl of HF/HNO3 acid; the material was condensed to 10 μl and was dried on a Si wafer. Since the size of the dried residue on the Si wafer was less than 1 cm in diameter, an incident X-ray beam with about 1 cm in width could effectively excite elemental components in such a small glass fragment. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…A number of studies have reported that comparisons of elemental compositions are useful for the forensic discrimination of glass fragments, 5,6,8,9,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and it is not pointed out again in this paper. What should be emphasized here is that a good correlation was observed in the elemental profiles between the non-heated and heated fragments in any of the 5 glasses.…”
Section: Comparison Of the Elemental Composition Between Heated And Nmentioning
confidence: 90%
See 1 more Smart Citation
“…A number of studies have reported that comparisons of elemental compositions are useful for the forensic discrimination of glass fragments, 5,6,8,9,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and it is not pointed out again in this paper. What should be emphasized here is that a good correlation was observed in the elemental profiles between the non-heated and heated fragments in any of the 5 glasses.…”
Section: Comparison Of the Elemental Composition Between Heated And Nmentioning
confidence: 90%
“…If tiny glass fragments found on the clothes of a suspect can be proved to originate from the broken window glass, they can be valuable physical evidence to associate the suspect with the crime. [1][2][3][4][5][6] The forensic glass comparison mentioned above has been conducted by measuring the refractive index (RI) [5][6][7][8][9][10][11][12][13][14] and conducting an analysis of the elemental compositions using procedures such as X-ray fluorescence spectrometry (XRF), 6,8,12,[15][16][17][18][19][20][21][22] inductively coupled plasma atomic emission spectrometry (ICP-AES) 8,15,[23][24][25] and mass spectrometry (ICP-MS). 5,6,9,12,18,[26][27][28][29] An RI measurement can be applied to a glass fragment smaller than 0.1 mm in a maximum width without its destruction.…”
Section: Introductionmentioning
confidence: 99%
“…However, since there are limitations regarding sample size, destruction of the glass fragment might be required. (1,61) Synchrotron radiation has been increasingly applied for the detection of trace elements to differentiate glass fragments. (58,59,62) amounts of heavy elements present in different samples; e.g.…”
Section: Glass and Soilmentioning
confidence: 99%
“…Glass fragments are often the most common pieces of trace evidence found at crime scenes, such as car accidents and burgled homes, which can be used to identify a suspect . Hence, previous studies have focused on distinguishing sources of broken glass using the physical and optical properties of the glass itself, such as color, thickness, and refractive index, because they involve simple preparation and short analysis time . With increased quality control in glass production, the physical and optical properties of glass have become regulated and now show less variation among products.…”
mentioning
confidence: 99%
“…[1,2] Hence, previous studies have focused on distinguishing sources of broken glass using the physical and optical properties of the glass itself, such as color, thickness, and refractive index, because they involve simple preparation and short analysis time. [3][4][5][6][7] With increased quality control in glass production, the physical and optical properties of glass have become regulated and now show less variation among products. Therefore, recent studies have used elemental analysis as an alternative discrimination tool.…”
mentioning
confidence: 99%